2021
DOI: 10.1021/acsaem.0c02640
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Effect of Nanoscale Porosity on Thermoelectric Power Factor of Si

Abstract: reducing the thermal conductivity. However, porosity also is detrimental to the thermoelectric power factor in the numerator of ZT. In this manuscript we derive strategies to recoup electrical performance in nanoporous Si by fine tuning the carrier concentration and through judicious design of the of pore size and shape so as to provide energy selective electron filtering. A semiclassical Boltzmann transport equation is used to model Si thermoelectric power factor. This model reveals three key results: The lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…But the overall effect of nanostructuring could be more complicated, involving the effect on ph, and phenomena such as energy filtering. 11,[32][33][34][35] For the latter, energy filtering either for majority or minority carriers would reduce bipolar effects (effectively increase the bandgap) and reduce the effect we describe.…”
mentioning
confidence: 99%
“…But the overall effect of nanostructuring could be more complicated, involving the effect on ph, and phenomena such as energy filtering. 11,[32][33][34][35] For the latter, energy filtering either for majority or minority carriers would reduce bipolar effects (effectively increase the bandgap) and reduce the effect we describe.…”
mentioning
confidence: 99%
“…The term is the Kronecker delta function, and is the first-order Bessel function of the first kind, and is the pore’s length perpendicular to the transport direction. We have previously computed the scattering matrix operators for pores with rectangular and triangular cross-sections and these can be found in reference [ 66 ]. The number density of pores is related to porosity, , and the pore size through the relationship , where is the volume of the pores.…”
Section: Charge Carriers Transport In Nanoporous Si 08 Ge 02mentioning
confidence: 99%
“…This is an insightful result, showing the systematic difference between discrete and extended pores on electron scattering processes. We have studied the effect of discreet (e.g., spherical) pores, on electronic coefficients in a recent paper [ 66 ]. There, we have shown that the low-energy scattering by pores induced a strong filtering effect that considerably enhances the Seebeck coefficient and thus mitigates the effect of nanoscale porosity on the thermoelectric power factor of dielectrics.…”
Section: Charge Carriers Transport In Nanoporous Si 08 Ge 02mentioning
confidence: 99%
“…Nanoengineered membranes including thin films, 2,3 nanowires, 4 nanomeshes, 5,6 nanocomposites, 7,8 and nanoporous structures [9][10][11][12] feature extremely low thermal conductivity, sometimes beyond the amorphous limit. 13 This is largely due to the scattering of phonons with large MFPs (generally with small frequencies), i.e., those that are comparable with the characteristic length of the material.…”
Section: Introductionmentioning
confidence: 99%